Swimming sprint performance depends on upper/lower limbs strength and swimmers level - Carvalho, D. D.; Monteiro, A. S.; Fonseca, P.; Silva, A. J.; Vilas-Boas, J. P.; Pyne, D. B.; Fernandes, R. J. (Journal of Sports Sciences, 2023)
Swimming performance is likely influenced by strength, but differences between butterfly, backstroke, breaststroke and front crawl, as well as between novice and expert swimmers, are unclear. We have examined the associations between sprint performances, upper and lower limb strength, and anthropometric characteristics in 14 (six males and eight females) non-elite and 16 (nine males and seven females) elite-level swimmers. After an anthropometric characterisation, participants performed four 25 m maximal swims (one per technique) with 10 min intervals, right and left shoulder flexion/extension isokinetic testing at 90 and 300º/s angular velocities and three countermovement jumps. Pearson correlation analysis showed that sprint times were moderate-largely negatively correlated with upper and lower limb strength and power (r ± 95%CI = 0.39 ± 0.26-0.77 ± 0.13, p < 0.05). Elite swimmers higher strength levels were associated with longer stroke length in butterfly and front crawl, and with higher stroke rate in backstroke and breaststroke (r ± 95%CI = 0.37 ± 0.32-0.68 ± 0.21; p < 0.05). Butterfly, backstroke and front crawl sprint times were moderate-largely negatively related with arm span (r ± 95%CI = 0.37 ± 0.26, 0.39 ± 0.25 and 0.69 ± 0.17, p < 0.05). The predictive model indicated that higher dry-land strength values distinguished elite from non-elite swimmers (r2 = 0.67-0.81; p < 0.001). This association was not observed per performance level and per sex, confirming that sprint swimming performance levels can be differentiated by dry-land strength testing.